Increasing the Material and Technical Competitiveness of Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is about transformation processes in many sectors of the socio-economic sphere as a result of the rapid development of new information technologies in the conditions of the digital economy, and the assessment of the level of competitiveness of enterprises to ensure the competitiveness of retail service enterprises in the service market and the implementation of strategic directions for ensuring competitiveness are the main points of the article.